Pseira VI : the Pseira Cemetery. - Betancourt, Philip P., 1936-; Davaras, Kōstēs (Prehistory monographs, 2002)
Richard B Seager excavated the Minoan cemetery on Pseira, a small island off the northeast coast of Crete, in 1907, although this work was never published. More recently, the Temple University excavations (1985-1994) under the direction of Philip P Betancourt and Costis Davaras conducted an intensive surface survey of the cemetery area, cleaned and drew plans of all the visible tombs, and excavated tombs that had not been previously investigated. The results of these new excavations are published in two volumes. This volume, Pseira VI, covers the methodology that was employed in the investigat.